Psoriatic Arthritis and Sarcopenia: A CrossSectional Ultrasonographic Study - Canan Doğan Tosun, Gonca; Güler, Tuba; Yurdakul, Fatma Gül; Balaban, Mehtap (Archives of Rheumatology, 2025)
Background/Aims: This study aims to identify sarcopenia and its associated factors in patients with psoriatic arthritis (PsA) and to assess the diagnostic utility of ultrasonography (USG) for identifying sarcopenia. Materials and Methods: The study included 54 PsA patients (21 males and 33 females; mean age: 46.5 ± 10.93; range, 18-65) and 55 age-, gender- and body mass index (BMI)–matched healthy controls (19 males and 36 females; mean age: 48 ± 11.30; range, 18-65). Demographic data, anthropometric measurements, functional assessments, handgrip strength, and 4-meter gait speed were evaluated. Disease activity was evaluated using the psoriatic arthritis impact of disease 12-item questionnaire (PSAID12), disease activity score 28 (DAS28), bath ankylosing spondylitis disease activity index (BASDAI), disease activity in psoriatic arthritis (DAPSA), and skin lesions with the psoriasis area and severity index (PASI). The thickness of bilateral rectus femoris, vastus intermedius, and quadriceps muscle were measured using USG. Whole-body muscle mass was analyzed via dualenergy x-ray absorptiometry. Results: Sarcopenia was diagnosed in 22 PsA patients (40.7%) and 12 healthy controls (21.8%). An association between sarcopenia, BMI, and disease duration was identified (P < .05). It was not associated with PSAID12, DAS28, BASDAI, DAPSA, PASI, age, gender, comorbidities, smoking, alcohol consumption, erythrocyte sedimentation rate, C-reactive protein, vitamin D levels, and history of falls. The USG measurements revealed that PsA patients with sarcopenia had lower thickness of rectus femoris, vastus intermedius, and quadriceps muscles (P < .05). Receiver-operating characteristic analysis was performed to determine the diagnostic cut-off values, which were as follows: right/left rectus femoris, 1.11 cm; right vastus intermedius, 1.17 cm; left vastus intermedius, 1.19 cm; right quadriceps, 2.31 cm; left quadriceps, 2.32 cm. Conclusion: The presence of sarcopenia was higher in PsA patients compared to healthy controls. The USG may be a practical and acceptable method for assessing muscle mass and diagnosing sarcopenia in patients with PsA.